ORGANIZATION OF OPERATION OF PAYMENT SYSTEMS AND ITS CURRENT STATE: UZBEKISTAN AND FOREIGN BANKING PRACTICES - Farkhod Makhmudov (Лучшие интеллектуальные исследования, 2024)
Abstract: A payment system is no more than an organized arrangement for transferring value between its participants. So defined, it is clear that payment systems are fundamental to the functioning of all monetary economies, no matter they are developed economies, transitional economies, or developing economies. The aim of this work is to show how the architecture of payment systems (payment instruments, processing, participants and etc.) influence to payment industry (microeconomic approach) and for the role of central bank in payment systems (macroeconomic - public approach). We use the method of qualitative analyses, not empirical measures. Central banks, as issuers of money, have always had a keen interest in the smooth functioning of the national payment system and the way it affects the economy. Their involvement has, however, evolved over time, as central banks have increasingly taken on a prominent role in the pursuit of the public good of maintaining trust in the currency and ensuring its smooth circulation. Consequently, their involvement in payment, clearing and settlement has changed.